A mixed edge-based smoothed finite element method (MES-FEM) for elasticity. (September 2016) - Leonetti, Leonardo; Garcea, Giovanni; Nguyen-Xuan, H.
Highlights: The element is simple accurate and robust in the analysis of elastic plane problems. The displacement interpolation is enriched by a revised Allman interpolation. The choice of the displacement interpolation keeps out zero-energy modes. The assumed stress is important in reducing the over-stiffness of linear triangles. Abstract: We propose a mixed smoothed finite element model for plane elasticity. Within each triangular element the displacement field is described by a revised Allman interpolation, while the stresses are assumed to be piece-wise constant on a background grid associated with the edges of the triangle. A straightforward implementation of the element, in order to make it easy to readily incorporate it in existing FE packages, is described. The numerical experiments show that the proposed model performs well and takes advantage of the enrichment of the displacement field. Moreover the drilling rotation parameters makes simple the extension to form shell elements.